2009
DOI: 10.1530/eje-08-0808
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of thyroid hormone status with myocardial function in stress cardiomyopathy

Abstract: Objective: This study aimed to investigate thyroid hormone (TH) status and its relationship with myocardial function as well as clinical and biochemical parameters in stress cardiomyopathy (CMP). Methods: Forty-five patients with stress CMP (the patient group), 31 patients without stress CMP (the control II group), and 58 healthy subjects (the control I group) were included. Sick euthyroid syndrome (SES) was defined as low total triiodothyronine (T 3 ) with normal TSH levels. Results: In the patient group at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…One proposed mechanism for this is the abrupt drop in estrogen levels following delivery, combined with a high physical and emotional stress state (41). However, other studies have found a correlation between lower T3 levels and myocardial contractility in patients with SIC (44). There may be gender-related differences in the autonomic nervous system that may partially explain the higher rates of this condition in women (42).…”
Section: Pathophysiologymentioning
confidence: 99%
“…One proposed mechanism for this is the abrupt drop in estrogen levels following delivery, combined with a high physical and emotional stress state (41). However, other studies have found a correlation between lower T3 levels and myocardial contractility in patients with SIC (44). There may be gender-related differences in the autonomic nervous system that may partially explain the higher rates of this condition in women (42).…”
Section: Pathophysiologymentioning
confidence: 99%
“…7 Furthermore, Lee SJ and colleagues showed influence of thyroid autoimmunity on myocardial contractility in stress cardiomyopathy. 8 Our patient had several autoimmune conditions. All these raise questions about relationship between autoimmune disease and pathogenesis of TCM.…”
Section: Lim T and Colleagues Reported A Case Of Tcm In Combinationmentioning
confidence: 76%
“…TC has been linked with many thyroid disorders, the most frequent being hyperthyroidism due to Graves–Basedow disease, but there are also reports in patients with hypothyroidism, euthyroid syndrome, thyroid surgery or thyroid cancer (6, 7). …”
Section: Discussionmentioning
confidence: 99%